2020
DOI: 10.31344/ijhhs.v4i4.208
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spiritual Meditation on Drug Addiction Recovery and Wellbeing: A Systematic Review

Abstract: It is well recognized throughout the history that religiosity, spirituality and the meditation practice have significant effects to the physical and mental health. Hence, this paper interested to evaluate the effectiveness of spiritual meditation on drug addiction recovery and its effects on psychological and mental health aspects. Three main databases in medicinal and psychology field were screened to identify the eligible studies which are PubMed, Cochrane and Scopus by using Boolean expression. Fourteen pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
3
0
1
Order By: Relevance
“…Spirituality was found to be the strongest predictor for CAM use especially amongst patients living with chronic disease. Particularly amongst people living with diabetes, cardiac conditions and cancer 10,13,14,15,16,40,41 . Spirituality and CAM are two topics that has gained recognition as being extremely relevant to cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality was found to be the strongest predictor for CAM use especially amongst patients living with chronic disease. Particularly amongst people living with diabetes, cardiac conditions and cancer 10,13,14,15,16,40,41 . Spirituality and CAM are two topics that has gained recognition as being extremely relevant to cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, psychiatric disorders and anxiety decrease in this period, and this reduction may have a positive effect on sexual function 33 . Kardi et al was shown religiosity, spirituality and the meditation practice have significant effects to the physical and mental health 34 .In the third trimester, concerns about childbirth and fetal health and the discomfort created by an enlarged stomach are exacerbated. In this period, the sexual activity of many couples is reduced or completely stopped and the couple's marital and sexual relationship is thus disrupted 35 Feeling physically unattractive, especially to the spouse, and an altered mental body image can lead to an unenjoyable sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, tinjauan sistematis dan meta-analisis Gonçalves dkk menyatakan bahwa intervensi spiritual mengurangi alkoholisme stres dan depresi (Gonçalves et al 2015). Meditasi berbasis mindfulness, meditasi berbasis mantra, latihan dua belas langkah, dzikir, terapi welas asih, merupakan program psikoterapi dengan unsur spiritualitas yang berada di bawah payung spiritual (Kadri, Husain, and Omar 2020). Meditasi spiritual memberikan dampak positif pada depresi, kecemasan (Bowen et al 2017), stres, gangguan stres pascatrauma (PTSD) (Lang et al 2012), kanker, skizofrenia, nyeri kronis (Lee et al 2012), gangguan hiperaktivitas defisit perhatian (ADHD) (Oliva et al 2021) dan kecanduan (Breslin, Zack, and McMain 2002).…”
Section: Literature Reviewunclassified